Strategi Pengembangan LKS Model Kausalitik Terintegrasi Nilai Karakter untuk Meningkatkan Kemampuan Berpikir Kreatif dan Perubahan Karakter - Huraiza Mahmudah; Joni Rokhmat; Kosim Kosim (Department of Physics Education, Universitas Mataram, 2022)
This study aims to identify a strategy for developing Character Value-Integrated Causal Model Student Worksheet ​​to improve creative thinking skills and change the character of junior high school students. Character value-integrated causal model ​​is a learning model that is used to develop students' potential in identifying and describing the causes and effects of a phenomenon or problem in everyday life related to the student's character. The research type is Research and Development with 4-D model encompassing define, design, develop, and disseminate. The result of this research is a design of a character value-integrated causal model Physics worksheet for business and simple machines materials for the 8th grade junior high school level. The strategy for developing a worksheet with character value-integrated causal model contains several unique characteristics, including: describing phenomena that contain several cause-effect elements, providing phenomena that are related to problems about character in everyday life to be identified, having a causality table, providing space for explanations, loading moral messages related to problems about character, using concise, clear, easily understood language, and using supporting images that are related to the phenomena described